O Papel das Novas Tecnologias na Educação Médica: Perceções relativas ao estudo da Anatomia com auxílio de computador - José Miguel Diniz Pereira Esteves de Oliveira (2020)
The paradigm shift in medical curriculum as well as the ever increasing influence of technology in pedagogical context challenge the traditional teaching process of core medical curriculum sciences, as is the case of Anatomy. In this context is relevant to understand students perspectives towards the implementation of new pedagogical approaches. This study evaluates the impact of the satisfaction with the implementation of a Computer Assisted Learning (CAL) training platform on the performance of medical students. Additionally, the present research aims to verify a potential dose-dependent effect between students' satisfaction performance and frequency of training through CAL platform, and, if present, measure its impact. A total of 671 medical students attending Musculoskeletal (MA) and Cardiovascular Anatomy (CA) courses were allocated to one of three groups (MA Group, CA Group, MA + CA Group). Students satisfaction was accessed using a validated questionnaire after each session. After the online training sessions, the students improved their perception towards CAL training, a trend that was observed in all three groups. Indeed, students' performance improved in the MA Group (Session 1 vs. Session 2: Part I 38,30 ± 5.06 vs. 39,98 ± 4.97 P < 0.001, Part II 17,60 ± 2.33 vs. 18,77 ± 2.55 P < 0.001, Part III 38,50 ± 5.14 vs. 40,30 ± 4.88 P < 0.001, Part IV 39,58 ± 4.53 vs. 41,44 ± 4.22 P < 0.001). The increase in satisfaction between session (Delta Perceptions score) showed a small positive correlation with the Musculoskeletal Anatomy training sessions in the MA Group (r = 0.259, P < 0.001) and a moderate positive correlation in the MA + CA Group (r = 0.366, P < 0.001). It also showed a small positive correlation with the Cardiovascular Anatomy training sessions CA Group (r = 0.198, P = 0.001). A positive dose-dependent effect between satisfaction and the number of training sessions was observed in both MA Group and CA Group.